2004
DOI: 10.1346/ccmn.2004.0520605
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and mineralogy of zeolitic tuffs from the Alaçatı (Çeşme) area, Turkey

Abstract: Silicic vitric tuffs of the Alaçatı (Çeşme) area, west of Izmir (Turkey), are partly altered to authigenic zeolites and clay minerals. Mordenite and clinoptilolite-heulandite accompanied by smectite are the main alteration products of the tuffs. Scanning electron microscope examination indicates that mordenite forms mainly from a gel-like precursor and to a lesser degree from volcanic glass. Mordenite and clinoptilolite-heulandite have formed by the hydrolysis and dissolution of silicic vitric tuffs by thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Well known zeolite deposits, especially of Cpt, are located in western and NW Turkey (Esenli & Özpeker, 1993;Helvacı et al, 1993;Gündogdu et al, 1996;Temel & Gündogdu, 1996;Esenli & Kumbasar, 1998;Kaçmaz & Köktürk, 2004;Kılıç & Kılıç, 2006;Snellings et al, 2008). The present study area is located SE of Ankara in the lacustrine Tuzgölü basin of Tertiary age which contains widespread volcanic and zeolite-bearing volcanoclastic rocks (Fig.…”
mentioning
confidence: 74%
“…Well known zeolite deposits, especially of Cpt, are located in western and NW Turkey (Esenli & Özpeker, 1993;Helvacı et al, 1993;Gündogdu et al, 1996;Temel & Gündogdu, 1996;Esenli & Kumbasar, 1998;Kaçmaz & Köktürk, 2004;Kılıç & Kılıç, 2006;Snellings et al, 2008). The present study area is located SE of Ankara in the lacustrine Tuzgölü basin of Tertiary age which contains widespread volcanic and zeolite-bearing volcanoclastic rocks (Fig.…”
mentioning
confidence: 74%
“…The main geological surveys starting with Kalafatçıoğlu (1961) in the Karaburun Peninsula are mainly related to pre-Neogene rock units (Çakmakoğlu and Bilgin, 2006). Few studies on Neogene carried out in the Çeşme Peninsula include magmatism (Innocenti and Mazzuoli, 1972;Borsi et al, 1972;Türkecan et al, 1998;Kaçmaz and Köktürk, 2004;Helvacı et al, 2009), hydrogeology-geothermal energy (Koçak, 1974;Yılmazer and Yakabağı, 1995;Gemici and Filiz, 2001) and Neogene geology (Besenecker, 1973;Göktaş, 2010Göktaş, , 2016b. Innocenti and Mazzuoli (1972) put forward that the "Alaçatı massif" (Armağandağı volcanics in this study) is represented by the calcalkaline character of latite-andesitic volcanics in their pioneering studies in which they examined petrochemical properties of the Neogene volcanics in the Karaburun Peninsula.…”
Section: Introductionmentioning
confidence: 99%
“…Besenecker (1973) showed that there were correlating equivalents of Neogene deposits of Chios Island in the Çeşme Peninsula by means of lithostratigraphic correlations and large mammal fossils. Kaçmaz and Köktürk (2004) examined the geochemical and mineralogical properties of "silicic vitric tuffs" (Alaçatı pyroclastics) near Alaçatı and stated that authigenic zeolitizations (mordenite, clinoptilotite-heulandite) developed in the parts subjected to partial alteration. The stratigraphies proposed for Neogene rock units in the Karaburun Peninsula by Türkecan et al (1998) and Helvacı et al (2009) were constructed based on the radiometric ages and it was accepted that the Neogene sedimentation and volcanism had developed in a laterally relationship from bottom to top.…”
Section: Introductionmentioning
confidence: 99%
“…The Neogene volcano-sedimentary units containing zeolites are widely located in Western Turkey. The presence of zeolites within these units is mostly associated with altered tuffs [2][3][4].…”
Section: Introductionmentioning
confidence: 99%